Development and validation of Indonesian peace of mind scale: The Rasch analysis - Wahyu Nanda Eka Saputra; Nur Hidayah; Muhammad Ramli; Adi Atmoko (International Journal of Evaluation and Research in Education (IJERE), 2023)
Every society dreams of true peace. To achieve true peace, humans need to start with inner peace. The importance of peace becomes one of the bases for developing a measure of peace for designing peace-building programs. This research answered the need for these measuring tools by developing and validating a peace measuring instrument called the Indonesian peace of mind scale (IPoMS). This instrument consists of seven items in two aspects: the internal state of peacefulness and harmony. This study used Rasch analysis to test the construct validity of IPoMS. The construct validity test involved 202 vocational high school students in Yogyakarta, Indonesia. Data analysis using Win step software provides information about the quality of respondents and instruments, items that are easy and difficult for respondents to agree on, fit order items, and unidimensionality. The results of the application of Rasch analysis showed that IPoMS is good, precise, and have item conformity with the model. IPoMS is a reliable and valid measuring tool to measure students’ level of peace accurately. This research discussed the implications and recommendations for further research for the implementation of guidance and counseling containing the value of peace as a follow-up to the performance of IPoMS.